2021
DOI: 10.3390/md19070381
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Carbohydrate Additives on the Growth Rate of Microalgae Biomass with an Increased Carbohydrate Content

Abstract: Our study focused on investigating the possibilities of controlling the accumulation of carbohydrates in certain microalgae species (Arthrospira platensis Gomont, Chlorella vulgaris Beijer, and Dunaliella salina Teod) to determine their potential in biofuel production (biohydrogen). It was found that after the introduction of carbohydrates (0.05 g⋅L−1) into the nutrient medium, the growth rate of the microalgae biomass increased, and the accumulation of carbohydrates reached 41.1%, 47.9%, and 31.7% for Arthros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 48 publications
(58 reference statements)
1
10
0
Order By: Relevance
“…The main primary metabolites of algae are lipids, proteins, carbohydrates, and water ( Table 1 ) [ 7 , 8 ]. Chlorophylls, cytochromes, nucleotides, and compounds that are intermediates in various metabolic reactions are also primary metabolites [ 8 ]. The biochemical composition of microalgae makes them suitable for producing various compounds.…”
Section: Introduction—characteristics Of Algaementioning
confidence: 99%
See 1 more Smart Citation
“…The main primary metabolites of algae are lipids, proteins, carbohydrates, and water ( Table 1 ) [ 7 , 8 ]. Chlorophylls, cytochromes, nucleotides, and compounds that are intermediates in various metabolic reactions are also primary metabolites [ 8 ]. The biochemical composition of microalgae makes them suitable for producing various compounds.…”
Section: Introduction—characteristics Of Algaementioning
confidence: 99%
“…In the life process, algae produce many secondary metabolites, which makes them an important natural source of these bioactive compounds [ 15 ]. The addition of preparations obtained from algae allows additional beneficial properties to be imparted to food products in addition to the traditional nutritional value [ 8 ]. Thus, functional nutrition with algae ingredients has a beneficial effect on human health, improving well-being and quality of life, as well as reducing the risk of diseases depending on the use of appropriate technologies to lyse cells and extract active products in mild conditions.…”
Section: Introduction—characteristics Of Algaementioning
confidence: 99%
“…The induction of resistance in plants by macroalgae polysaccharides is an effective method for disease control against environmental constraints which is linked to the activation or enhancement of several plant defense mechanisms such as the positive regulation of the expression of defense genes involved in the response of a wide range of abiotic and biotic stress, and the induction of the antioxidant system and the production of secondary metabolites [ 54 , 56 , 57 , 58 ]. Alginate or alginate oligosaccharides are the most algae carbohydrates described as potent elicitors in the literature ( Table 2 ).…”
Section: Elicitation and Biostimulationmentioning
confidence: 99%
“…Studies have shown that microalgae can remove various pollutant from wastewater, such as oxygen consuming pollutants, nitrogen, phosphorus, heavy metals, organic matter, and absorb harmful gases such as NO X , SO X , and H 2 S at a certain concentration. The biomass harvested from wastewater treatment can also be utilized as raw materials for biofuel, feed, and chemical compounds [4][5][6][7][8][9]. Microalgae can use CO 2 during photosynthesis as the only carbon source for heterotrophic growth and can use external carbon sources for heterotrophic growth to improve the biomass and oil content of microalgae [10,11], which can greatly reduce global emissions of greenhouse gases such as CO 2 [12].…”
Section: Introductionmentioning
confidence: 99%